Infrastructure for Digital Pasture-Based Livestock Production in Arid Zones - S. S. Dorzhiev; E. G. Bazarova (Сельскохозяйственные машины и технологии, 2025)
The current global economic and environmental context, which is characterized by desertification, land degradation, climate change, and ecosystem disruption, necessitates urgent action in sustainable land use. While pasture-based livestock farming offers numerous advantages, free-range grazing presents several labor-intensive challenges, such as locating and tracking animals, monitoring livestock health, mitigating the risk of loss in wild environments, and regulating grazing pressure on pastures. (Research purpose) To develop a digital pasture infrastructure as a universal, integrated system with autonomous energy and water supply, aimed at automating auxiliary processes in pasture-based livestock farming. (Materials and methods) Various approaches to improving pasture efficiency were reviewed. The analysis revealed that existing technologies typically address isolated aspects, such as water supply, pasture rotation, or livestock monitoring. However, they lack a comprehensive system that integrates the entire pasture infrastructure and the interactions among its components. (Results and discussion) A digital pasture concept based on renewable energy sources is proposed. An integrated infrastructure model for pasture-based and transhumant livestock farming was developed. The system consists of distinct infrastructure modules, including communication, monitoring, water supply, electrification, transportation, a central dispatch unit, and a supplemental feeding unit. Several components were developed and patented, including individual livestock blankets equipped with condition sensors, a monitoring station, a wind power unit, and an atmospheric water extractor. The monitoring station, capable of data collection, control, monitoring, and communication using renewable energy, was field-tested in the Astrakhan Region. The sensor-equipped livestock blankets were tested on a pilot group of calves in the Yaroslavl Region. Field trials of the atmospheric moisture extractor were also conducted. Additional trials are underway in southern regions and the Moscow Region to evaluate the performance of a multi-unit wind energy complex designed for areas with low wind potential. (Conclusions) The modular architecture of the proposed system enables flexible integration of various technologies and functional units, adaptable to the specific needs of local production conditions. The development and implementation of a digital, intelligent infrastructure for pasture-based and transhumant livestock farming, based on resource-efficient, nature-based, and digital technologies, offers a timely and innovative solution.